2020
DOI: 10.1590/1982-0224-2020-0013
|View full text |Cite
|
Sign up to set email alerts
|

Comparative cytogenetic analyses in Ancistrus species (Siluriformes: Loricariidae)

Abstract: Ancistrus is a specious genus of armored catfishes that has been extensively used for cytogenetic studies in the last 17 years. A comparison of the extensive karyotypic plasticity within this genus is presented with new cytogenetic analysis for Ancistrus cf. multispinis and Ancistrus aguaboensis. This study aims to improve our understanding of chromosomal evolution associated with changes in the diploid number (2n) and the dispersion of ribosomal DNAs (rDNAs) within Ancistrus. Ancistrus cf. multispinis and A. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(57 citation statements)
references
References 61 publications
6
42
0
Order By: Relevance
“…The Loricariidae family is an outstanding group to investigate chromosomal breaks and rearrangements that gave rise to extremely diverse karyotypes among its representatives [ 39 , 40 , 41 , 42 ]. These fishes are characterized by a sedentary lifestyle, with rare migratory events [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Loricariidae family is an outstanding group to investigate chromosomal breaks and rearrangements that gave rise to extremely diverse karyotypes among its representatives [ 39 , 40 , 41 , 42 ]. These fishes are characterized by a sedentary lifestyle, with rare migratory events [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been repeatedly shown that populations of many teleost species and species complexes are polymorphic for sex chromosome systems [31,59,65,70,79,[83][84][85][86][87][88][89]. These observations point to a very recent, ongoing and recurrent formation of multiple sex chromosomes and stress the importance of proper sampling and sample size.…”
Section: Y-a Tandem Fusionmentioning
confidence: 99%
“…This is evidenced by a recent report of experimental crosses between a strain of the platyfish Xiphophorus maculatus with XY and the swordtail Xiphophorus helleri with ZW, which led to the translocation of the sex-determining region to an autosome in hybrids [ 145 ]. It is therefore reasonable to hypothesize that interaction between populations differing in their sex chromosome systems [ 31 , 59 , 65 , 70 , 79 , 83 , 85 89 ] can give rise to novel sex chromosomes including multiple sex chromosome systems.…”
Section: Evolutionary Pathways Of Teleost Multiple Sex Chromosomes: Current State Of Knowledge and Further Research Directionsmentioning
confidence: 99%
“…In addition, Ancistrini species exhibit great differences in terms of number and positions of rDNAs sites. For example, a single chromosome pair carrying 18S rDNA is a characteristic shared by all analyzed Ancistrus Kner, 1854 species [Bueno et al, 2018;Glugoski et al, 2020]. On the other hand, Pety et al [2018] found multiple sites for 18S rDNA in Peckoltia species, another genus of Ancistrini.…”
Section: Introductionmentioning
confidence: 98%
“…Several cytogenetic studies involving Ancistrini species point to conservation of the diploid number of 2n = 52 chromosomes [Bueno et al, 2018;Pety et al, 2018;Glugoski et al, 2020], but differences in the karyotype formulae suggest inversions as the primary mechanisms of chromosomal evolution in this group [Ayres-Alves et al, 2017;Bueno et al, 2018]. In addition, Ancistrini species exhibit great differences in terms of number and positions of rDNAs sites.…”
Section: Introductionmentioning
confidence: 99%